Perancangan Sistem Informasi Portal Sekolah - M. Rafly Rifai; Hazas Selis Yuke; Khoirul Anam; Habib M Furqon (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
The existence of a school website is very important to make it easier to get the information needed by schools, teachers, students and the community. With the website, information can be easily managed by the school community. For example, school operators can input this information through the website portal so that people can read the information effectively and efficiently without having to come to school. In addition, the public can download documents through the website. In addition, this website allows for easy communication between teachers, students and administrators. Other features are lesson schedules and teacher data, other community data. This website provides many benefits for the community as well as convenience in managing information systems by operators.